IMPLEMENTATION OF THE DHUHA PRAYER PROGRAM IN FOSTERING STUDENT DISCIPLINE: A CASE STUDY IN ISLAMIC JUNIOR HIGH SCHOOLS - Irawan, Deni; Herrian, Aulia Dwi Putri; Ramadani, Ayu; Syarifah; Wiguna, Satria (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study explores the implementation of the Dhuha prayer program and its role in fostering student discipline at Islamic junior high schools. The research employs a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, and validated using triangulation techniques to ensure reliability. The findings reveal that the Dhuha prayer program is conducted routinely before the start of classes and has become a distinctive feature of the school’s religious culture. The program effectively cultivates student discipline, as reflected in punctuality, orderly participation in worship, and increased responsibility in academic tasks. Moreover, it enhances teacher–student relationships and promotes a spiritual atmosphere within the school environment. The main challenges encountered include student tardiness, lack of focus during prayer, limited facilities, a tight academic schedule, and insufficient parental support. Overall, the Dhuha prayer program significantly contributes to strengthening student character and discipline formation. Penelitian ini mengkaji implementasi program salat Dhuha dan perannya dalam menumbuhkan kedisiplinan siswa di madrasah tsanawiyah. Pendekatan penelitian yang digunakan adalah kualitatif dengan desain deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian divalidasi menggunakan teknik triangulasi untuk menjamin keabsahan data. Hasil penelitian menunjukkan bahwa program salat Dhuha dilaksanakan secara rutin sebelum kegiatan belajar dimulai dan telah menjadi ciri khas budaya religius sekolah. Program ini efektif menumbuhkan kedisiplinan siswa, yang tampak dari kebiasaan datang tepat waktu, ketertiban dalam beribadah, serta meningkatnya tanggung jawab terhadap tugas belajar. Selain itu, kegiatan ini juga mempererat hubungan antara guru dan siswa serta menciptakan suasana spiritual di lingkungan sekolah. Adapun kendala yang dihadapi meliputi keterlambatan siswa, kurangnya kekhusyukan dalam salat, keterbatasan fasilitas, padatnya jadwal belajar, dan minimnya dukungan dari orang tua. Secara keseluruhan, program salat Dhuha memberikan kontribusi signifikan terhadap pembentukan karakter dan disiplin siswa.